Exploring the potential of historical images for the investigation of glacier changes: the case of Belvedere Glacier, Italian Alps - Kropáček, Jan; Nüsser, Marcus; Schmidt, Susanne (Acta Universitatis Carolinae. Geographica, 2024)
Historical images dispersed in various archives can be instrumental in documenting processes connected to glacier changes in mountains. A series of more than 29 engravings and photographs of the Monte Rosa east face have been found covering the period since 1789. Some images were produced by a combination of photography and engraving, a common approach before practical techniques for printing halftone images were introduced. Using a repeat photography approach, the present study documents the changes in the extent and debris cover of the Belvedere Glacier. Based on visual comparison of images, it appears that the debris cover of the lower part of the glacier developed mainly during the period of the 1860s-1880s. Furthermore, the image series documents the evolution of the terminus both in terms of elevation and shape, as well as a breach in lateral moraine which could be dated back to the end of the 19th century, well before the reported glacier lake outburst flood in 1904.